Restrictions and export duties: A pending issue - Illescas, Nelson; Jorge, Nicolás (Instituto Interamericano de Cooperación para la Agricultura, 2021)
Export barriers (or controls) can take a variety of forms -such as prohibitions, taxes, quotas or licenses, among others- and have been applied to industrial and agricultural products, both by developed and developing countries, while pursuing economic and non-economic goals. When both the Havana Charter - legal instrument intended to establish the International Trade Organization37- and the General Agreement on Customs Tariffs and Trade - GATT - were negotiated, measures of this type were not a major issue of concern.